Heightened cholesterol 25-hydroxylase expression in aged lung during Streptococcus pneumoniae - Thomas, David G.; Yang, Jianjun; Cho, Soo Jung; Stout-Delgado, Heather (Frontiers in Aging, 2024)
IntroductionAlveolar macrophages (AM) are critical effectors of the immune response and are essential for host responses to Streptococcus pneumoniae. Changes in lipid metabolism in AM can alter cellular function and biology. Impaired metabolism can contribute to excessive lipid accumulation and pro-inflammatory signaling. Our current study was designed to examine the role of cholesterol 25-hydroxylase (Ch25h), a redox enzyme that catalyzes the oxidation of cholesterol to 25-hydroxycholesterol (25-HC), in modulating AM responses in the aged lung during S. pneumoniae infection.MethodsTo observe the impact of aging on Ch25h expression in AM during infection, in vitro and in vivo murine models of S. pneumoniae were used.ResultsAt baseline and in response to infection, cholesterol metabolism significantly altered in aged AM, which corresponded with increased lipid droplet formation. In vitro, treatment of aged macrophages with Ch25 h-specific siRNA improved S. pneumoniae clearance and enhanced phagocytic receptor expression. In vivo siRNA targeting significantly reduced Ch25h expression in aged lungs and improved clinical parameters during S. pneumoniae infection. Reduction of Ch25h was associated with changes in phagocytosis and antibacterial signaling, correlated with changes in cholesterol metabolism, and increased S. pneumoniae clearance.DiscussionThe results of our current study demonstrate that Ch25h plays an essential role in modulating aged AM responses to S. pneumoniae.